MONEY SUPPLY AND FINANCIAL PERFORMANCE OF DEPOSIT TAKING SACCOS IN KENYA - David Irungu Thugu; Gordon Opuodho (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
The Savings and Credit Cooperative Societies (SACCOs) are among the most prominent cooperative societies in Kenya, distinguished by unique traits compared to other cooperatives. In Kenya, Deposit-Taking (DT)-SACCOs have experienced a decline in growth rates concerning key performance parameters such as total assets, total deposits, and gross loans. Firms make various operational and strategic decisions—including financing, investing, and operational decisions that are typically moderated by the macroeconomic environment. However, many SACCOs operate without understanding the effect of macroeconomic variables, such as money supply, on their financial performance. This study aimed to establish the effect of money supply on the financial performance of savings and cooperative societies in Kenya. A causal research design was utilized, targeting all 184 deposit-taking SACCOs in Kenya. The study relied on secondary data for a ten-year period (2015-2024) and employed a panel data analytical model. The findings revealed a significant positive relationship between money supply and financial performance of DT-SACCOs in Kenya. Based on these findings, the study concludes that money supply has a statistically significant positive effect on the financial performance of DT-SACCOs in Kenya. Therefore, it is recommended that all SACCOs in Kenya should consider the impact of macroeconomic predictors to enhance financial performance. Additionally, policymakers and the Central Bank of Kenya should maintain stable and adequate liquidity to support the financial performance growth of DT-SACCOs.